Strength of Materials Teaching from Active Learning - Andreatta-da-Costa, Luciano (Revista Insignare Scientia - RIS, 2021)
This paper presents the results of research conducted in the area of engineering education based on active learning from a hands-on experiment determining the Young’s modulus of rubber bands. This research primarily aims to evaluate the extent to which active learning contributes to a better understanding of the Young’s modulus. The theoretical framework emphasises the need for student action in knowledge-building. A hypothesis test for proportions was used to compare the average scores obtained by students from two groups on a test given at the end of each pedagogical intervention. The first group (control group) took traditional lecture-based classes, and the second group took classes combined with a hands-on experiment using rubber bands. The results showed a significant improvement in the students who conducted the practical experiment for questions of a conceptual nature and a statistical difference between the performance for the conceptual questions and calculation questions in both groups.